An inflammatory memory and angiogenic self-assembling nanofiber hydrogel scaffold seeded with Akkermansia muciniphila to accelerate the healing of diabetic ischemic ulcers. Issue 31 (14th May 2018) - Cheng, Panke; Yao, Liyang; Chen, Xiaolong; Su, Xingxing; Su, Xuejiao; Huang, Qiang; Hou, Chunli
Abstract : In this research, a polypeptide skeleton was synthesized based on 3, 4-dihydroxyphenylalanine (DOPA) and conjugated with inflammatory and angiogenesis peptides, combined with A. Muciniphila as a novel strategy for diabetic ischemic ulcer treatment. Abstract : Refractory ulcers are a major challenge in the treatment of a diabetic foot, because of the immunodeficient, ischemic and high-glucose microenvironment. Inflammatory memory peptides, which were extracted from the immune mediator absent in melanoma 2 (AIM2), could effectively improve the immunodeficient microenvironment and special angiogenic peptides could effectively promote angiogenesis. Moreover, the gut flora Akkermansia muciniphila ( A. muciniphila ) participates in diabetic metabolism and could decrease high-glucose levels. In this research, a polypeptide skeleton (PPS) was synthesized based on 3, 4-dihydroxyphenylalanine (DOPA) and peptides, forming the hydrophilic and hydrophobic parts. Inflammatory memory peptides and angiogenic peptides were synthesized and conjugated with the PPS, which then formed an anisotropic hydrogel through the self-assembling of β-sheet peptides based on hydrophobicity and DOPA oxidation. A. muciniphila was seeded into the hydrogel and transported into diabetic ischemic ulcers through subcutaneous injection, and the healing of diabetic ischemic ulcers was promoted. The inflammatory memory peptides were released based on the A. muciniphila enzyme response, and they firstly improved the immunity of the local surroundings. Then, the angiogenic peptides were also released through irradiation and they promoted angiogenesis. Additionally, the transported A. muciniphila could decrease the local glucose levels and spontaneously regress once the diabetic ischemic ulcers had healed. A. muciniphila combined with a functional polypeptide hydrogel may be a novel strategy for diabetic ischemic ulcer treatment.